Effects of cervical transcutaneous Vagus Nerve Stimulation (ctVNS) on military cognitive performance during sleep deprivation - Bottenheft, C.; Fonken, Y. M.; Hendrikse, L. F.; Koedijk, M.; Landman, A.; Binsch, O. (Frontiers in Physiology, 2025)
IntroductionMaintaining cognitive performance during sleep deprivation is of vital importance in many professions, especially in high-risk professions like the military. It has long been known that sleep deprivation diminishes cognitive performance. To mitigate the negative effects on cognitive performance during crucial military tasks, new interventions are necessary. Non-invasive cervical transcutaneous vagus nerve stimulation (ctVNS) has gained traction as a method to boost alertness and cognitive functioning.MethodsWe investigated the effects of a 2 × 2 minute ctVNS stimulation protocol on three cognitive tasks applied during conditions of sleep-deprivation: a psychomotor vigilance task (PVT), a multitasking task (SynWin), and an inhibitory control task (stop-signal task; SST). In addition, participants also performed a close-quarter-battle (CQB) test in virtual reality (VR) to examine if potential effects of ctVNS translate to operational military contexts. A total of 35 military operators from Special Operations Forces (SOF) and SOF support units participated. They were randomly assigned to an active stimulation group or sham group. Before stimulation at 19:00 h, participants performed baseline tests. Participants stayed awake through the night and performed the cognitive tasks every 3 h. The last round of cognitive tasks was followed by the VR test.ResultsThough sleep deprivation was successfully induced, as evident from a decline in performance on all three cognitive tasks (effect of session: p < 0.001 SynWin; p < 0.001 PVT; p < 0.001 SST; Linear Mixed Model), no significant effects of ctVNS were found on cognitive task performance, as well as on the military operational VR task. However, the influence of stimulation intensity on SynWin performance showed a trend, indicating that higher stimulation intensities could have a negative impact on cognitive performance.DiscussionA 2 × 2 minute stimulation protocol may not be sufficient to elicit beneficial effects on cognitive-and operational military performance. Moreover, correct stimulation intensity may be critical to induce effects on cognitive performance, as stimulation effects may follow an inverted-u dose-response curve. Stimulation intensities in the current study are higher compared to a similar study that reported beneficial effects of ctVNS, which may explain this null finding. Further research is recommended to optimize stimulation protocols and investigate robustness of effects.